Solid-Liquid Phase Transfer Catalysis and Microwave-Assisted Green Synthesis of Tetracyclone - Kasséhin, Urbain C.; Gbaguidi, A. Fernand; Carato, Pascal; McCurdy, Christopher R.; Accrombessi, Georges C.; Poupaert, Jacques H. (My University, 2015)
A green synthesis of tetracyclone (2, 3, 4, 5-tetraphenyl-2, 4-cyclopentadien-1-one) has been conceived and executed on the basis of a rationale design. Three separate, “green” processes to synthesize tetracyclone were undertaken to compare homogeneous and heterogeneous reaction conditions as well as to examine the efficacy of microwave enhancement and the utility of phase transfer catalysis. Our mechanistically-based approach involves a unique solid-liquid phase transfer catalysis, microwave activation, and nucleophilic catalysis involving anthranilic acid as a green catalyst. Use of these methods collectively resulted in a yield of 82% for the title compound with a minimal resultant waste stream.
Keywords: Tetracyclone (2; 3; 4; 5-tetraphenyl-2; 4-cyclopentadien-1-one); Microwave-Activation; Tetracyclone thiosemicarbazone derivatives; Diels–Alder-Reaction; Nucleophilic catalysis